Synthesis Of Cobalt/Gold Bimetallic Hollow Microspheres And Its Optical Properties - Khe, Cheng Seong; Aziz, Azizan; Lockman, Zainovia (2011)

(untitled)
Galvanic replacement reaction is a very simple and effective method to prepare the particles with hollow interior [1].